Reclaiming Being: Applying a Decolonial Lens to Gendered Violence, Indigenous Motherhood, and Community Wellbeing - Leslie Dawson (Societies)
Indigenous women and children in Canada are significantly more likely to experience some form of family violence than their non-Indigenous counterparts. However, biomedical and academic discussions around the violence that Indigenous women and their families and communities face reflect a colonial narrative emphasizing Euro-Canadian perspectives and values; a colonial narrative that disconnects the role of past and ongoing forms of colonial violence and naturalizes family violence within Indigenous communities, informing a view of Indigeneity as risk. Through a decolonial lens, the underlying causes of family violence in Indigenous communities can be connected to the gendered violence of patriarchal colonialism targeting Indigenous women. It is revealed how Indigenous women’s bodies became a site of the coloniality of violence as colonization disenfranchised and displaced Indigenous women from their lands, communities, and central roles. Gendered colonial violence attacked Indigenous women’s scared status in their societies and disrupted Indigenous relational modes of being. This informed a coloniality of being for Indigenous peoples; a coloniality of being integral to intergenerational trauma and family violence. Through the lens of Indigenous laws as a decolonial approach to family violence, the centrality of Indigenous women’s roles and responsibilities as mothers is linked to community wellbeing and intertwined with leadership and governance. By grounding the rights of Indigenous women within relationships, Indigenous women can reclaim their sacred places within respectful, reciprocal, and interconnected ways of being.